(untitled) (Andamios, Revista de Investigación Social, 2016)
In this paper we intend to briefly analyze the idea of dialogue of knowledge, translation, and hegemonic articulation. We will examine some of their dimensions and explore their possibilities for eventual development, through an exercise of discovering the critical relations between them. The central thesis is that they are notions that are non-exclusive amongst themselves, yet they are not equivalent. Rather, they correspond to distinct levels of contact and articulation among sociocultural differences. Recognizing these differences, as well as the possible relations between these concepts, could lead to fertile advances in the task of reflection and the collective construction of alternative forms of intercultural contact that are more just, equal, and democratic, during a time when global neoliberal capitalism has acquired expressions ever more expansive, colonialist, and predatory.